Peuplements benthiques des substrats meubles du Sud de la Mer Egée - Vamvakas, C-N.E. (Tethys, 1970)
Study of the benthic populations of the bathyal mud in the South Aegean Sea (Eastem Mediterranean) is undertaken and a comparison is made with identical populations put out by PICARD in Marseilles région (Western Mediterranean) in 1965. The material has been hauled and examined according to PICARD'S method (1965). The regions studied are : Santorin Archipelago, Cassos strait, Cythere (Cerigo) and Anticythere straits, Epidaurus hollow (Saronic Gulf or Gulf of Athens), as well as two régions of the Northern and Southern coasts of Crète (HerakBon Gulf and Lithinon Cape). The results obtained can be summarized as follows : 1/ The scarcity of species and of individuals is évident. 2/ The dominance of some species and of some systematic groups is modified. 3/ Some caracteristic species of the biocoenosis VP (deep mud) colonies lesser depths whereas characteristic species of the VTC biocoenosis (coastal terrigenous mud) are présent in greater depths. 4/ The VP biocoenosis looses its individuality and is mixed with the VTC biocoenosis which by itself does not have a clear individuality. Thus, the populations are in biocoenotic balance.
Kristian Fauchald's Polychaeta DB